Nanotechnology in Plant Science: To Make a Long Story Short - Sanzari, Ilaria; Leone, Antonietta; Ambrosone, Alfredo (Frontiers in Bioengineering and Biotechnology, 2019)
This mini-review aims at gaining knowledge on basic aspects of plant nanotechnology. While in recent years the enormous progress of nanotechnology in biomedical sciences has revolutionized therapeutic and diagnostic approaches, the comprehension of nanoparticle-plant interactions, including uptake, mobilization and accumulation, is still in its infancy. Deeper studies are needed to establish the impact of nanomaterials (NMs) on plant growth and agro-ecosystems, and to develop smart nanotechnology applications in crop improvement. Herein we provide a short overview on NMs employed in plant science and concisely describe key NM-plant interactions in terms of uptake, mobilization mechanisms and biological effects. The major current applications in plants are reviewed also discussing the potential use of polymeric soft NMs which may open new and safer opportunities for smart delivery of biomolecules and for new strategies in plant genetic engineering, with the final aim to enhance plant defense and/or stimulate plant growth and development and, ultimately, crop production. Finally, we envisage that multidisciplinary collaborative approaches will be central to fill the knowledge gap in plant nanotechnology and push towards the use of NMs in agriculture and, more in general, in plant science research.